Effect of co-processed excipient type on properties of orodispersible tablets containing captopril, tramadol, and domperidone - Tranová, Thao; Loskot, Jan; Navrátil, Ondřej; Brniak, Witold; Mužíková, Jitka (International journal of pharmaceutics, 2023)
An important feature of orodispersible tablets (ODTs) is the convenient administration of the drugs, in some cases, faster onset of action, stability maintenance, and dose precision. This work focused on the preparation of ODTs containing mannitol-based co-processed excipients Prosolv® ODT G2, Ludiflash® and Parteck® ODT in combination with tramadol, captopril, and domperidone by direct compression. Prosolv® ODT G2 showed high energy of plastic deformation due to the content of microcrystalline cellulose. Parteck® ODT provided compact tablets due to the content of granulated mannitol. All drugs decreased tensile strength, increased friability, prolonged disintegration time, and decreased the porosity of tablets. Tablets containing Prosolv® ODT G2 with captopril, domperidone, and tramadol; and Parteck® ODT with domperidone met the requirements for ODTs production, i.e., friability ≤ 1% and disintegration time ≤ 180 s, fast wetting time, high water absorption ratio, and adequate tensile strength. The disintegration time was tested using both the pharmacopeial method and the BJKSN-13 apparatus. The results indicate the significant difference between these methods, with the disintegration time being longer when tested with the BJKSN-13 instrument.
Keywords: Mannitol; Orodispersible tablets; Disintegration time; Captopril; Domperidone; domperidon; Compactability; pomocné látky; tramadol; Solubility; tablety; rozpustnost; Energy profile of compression; příprava léků; mannitol; Co-processed excipients; aplikace orální; Tomography; Tramadol; Excipients; Drug Compounding; Administration, Oral; Tablets; kaptopril